A produção orgânica na agricultura familiar: motivações, desafios e perspectivas em Botucatu – SP - Pimentel, Gabriela Carrara (Universidade Federal de São Carlos, 2025)
This study aims to analyze the main motivations, challenges, and benefits of organic production among family farmers in the municipality of Botucatu – SP, seeking to understand how this practice is consolidating itself as a sustainable alternative to the conventional model of agricultural production. The study is based on the growing need to rethink the current agro-industrial system, originating from the Green Revolution, whose productive expansion has generated significant socioenvironmental impacts, such as soil degradation, biodiversity loss, and the exclusion of small producers. The methodology adopted was qualitative and descriptive, based on semi-structured interviews with family organic producers active in municipal fairs and regional associations. The analyses were complemented by secondary data on public incentive policies – such as the National School Feeding Program (PNAE), the Food Acquisition Program (PAA), and the National Plan for Agroecology and Organic Production (PNAPO). The results indicate that the main motivations for adopting organic production are linked to family health, environmental preservation, and the continuity of traditional practices transmitted between generations. It was found that, despite the financial and bureaucratic difficulties related to certification and the lack of consumer recognition, producers perceive significant gains in terms of quality of life, job creation, and sustainability in their agricultural practices. It is concluded that organic family farming represents a strategy of resistance and transformation, linking economic production, environmental responsibility, and social inclusion, whose expansion depends on the strengthening of public policies and the technical training of producers.
Organic production in family farming: motivations, challenges, and perspectives in Botucatu, São Paulo
Keywords: Agricultura orgânica; Agricultura familiar; Sustentabilidade; PNAPO; Agroecologia; Políticas públicas; Organic agriculture; Family farming; Sustainability; Agroecology; Public policies; CIENCIAS HUMANAS::SOCIOLOGIA::SOCIOLOGIA RURAL; 2. Fome Zero e Agricultura Sustentável